O11.5 Impact of HIV self-testing on the promotion of HIV testing among men who have sex with men in china: a randomized controlled trial. (14th July 2019) - Cheng, Weibin; Friedman, Mackey; Egan, James; Hampton, Melvin; Zhong, Fei; Xu, Huifang; Stall, Ron
Abstract : Background: HIV self-testing offers a novel opportunity to increase HIV testing among MSM in China. We conducted a randomized controlled trial to evaluate if access to HIV self-testing materials would increase testing behavior among MSM in China. Methods: We randomized 491 HIV-negative MSM into either an intervention (n=250) or control group (n=241). The intervention group received free self-testing materials, while the control group was refer to test at local facilities. Both groups then received HIV testing reminders three and six months every three months. HIV testing results were verified via the HIV testing database in Guangzhou. Completed-records analyses and intention-to-treat with multiple imputation were used to determine the efficacy of self-testing in promoting HIV testing. Sensitivity analyses were further performed to exclude individuals from the control group who had used a self-test since randomization to reduce spurious findings. Results: HIV testing results were obtained for 91.2% of the sample (n = 448), with information obtained for 88.4% (n = 213) of the control group and 94.0% (n = 235) of the intervention group. Within the final sample, 73.7% (n = 330) had received an HIV test within the period of assessment, with 27.7% (n = 124) of the sample reporting use of an HIV self-test (35.7% in the intervention group versus 18.8% in the control group, χ 2 =12.73, P <0.001). HIV Self-testing produced a 24.8% (95%CI: 10.0, 39.7.) increase in HIV testing in intervention group compare with control group. Likewise, individuals in the intervention group were 3.10 (95%CI: 2.06, 4.65) times more likely to receive an HIV test than control group participants. Conclusion: HIV self-testing as a supplement to existing facility-based testing services is useful in increasing HIV testing among MSM in China. More research is necessary to assess the long-term feasibility of providing HIV self-testing materials to MSM in China as an effective HIV prevention tool. Disclosure: No significant relationships.